2006
DOI: 10.1007/s10549-006-9191-2
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of genistein and apigenin on the growth of breast cancer cells correlates with their ability to activate ER alpha

Abstract: Genistein and apigenin are phytoestrogens present in commercial preparations used for the treatment of postmenopausal symptoms. In this study, we assessed the influence of these compounds on mammary tumor growth. Both compounds stimulate the proliferation of MCF-7 and T47D cells [estrogen receptor alpha (ERalpha-positive)], but do not stimulate the proliferation of an ERalpha-negative cell line (MDA-MB-435 cells). Genistein appeared more efficient in this regard due to its higher binding affinity for ERalpha, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 65 publications
4
74
0
2
Order By: Relevance
“…Note in this context that bioavailability and metabolism of phytoestrogens in their response variability is also a topic needing further investigation (de Cremoux 2010) Isoflavones modulate steroid receptors status (ER, PR, and AR) according to their administration dose, as well as their duration of action, which may be transient and extremely rapid or maintained for a long period (Kampa et al, 2007, Pritchett et al, 2008, Zhang et al, 1999. In this regard, genistein, which at low concentrations enhances ER-dependent proliferation of ERa-positive cells in breast cancer in vitro models in an estrogen response element (ERE)-dependent manner, (Seo et al, 2006),, in vivo and in the presence of low levels of circulating estrogen, acts in an additive manner to stimulate tumor growth, suggesting interactions with multiple estrogen sites (Bentrem et al, 2003). Whatever could be the underlying mechanism, this observation indicates that consumption of products containing genistein may not be safe for postmenopausal women with estrogen-dependent breast cancer.…”
Section: Effects Of Isoflavone-rich Foodsmentioning
confidence: 99%
“…Note in this context that bioavailability and metabolism of phytoestrogens in their response variability is also a topic needing further investigation (de Cremoux 2010) Isoflavones modulate steroid receptors status (ER, PR, and AR) according to their administration dose, as well as their duration of action, which may be transient and extremely rapid or maintained for a long period (Kampa et al, 2007, Pritchett et al, 2008, Zhang et al, 1999. In this regard, genistein, which at low concentrations enhances ER-dependent proliferation of ERa-positive cells in breast cancer in vitro models in an estrogen response element (ERE)-dependent manner, (Seo et al, 2006),, in vivo and in the presence of low levels of circulating estrogen, acts in an additive manner to stimulate tumor growth, suggesting interactions with multiple estrogen sites (Bentrem et al, 2003). Whatever could be the underlying mechanism, this observation indicates that consumption of products containing genistein may not be safe for postmenopausal women with estrogen-dependent breast cancer.…”
Section: Effects Of Isoflavone-rich Foodsmentioning
confidence: 99%
“…For example, genistein can interfere with tamoxifen's ability to inhibit tumor growth, whereas daidzein can enhance it. 131,132 Dietary elements such as carbohydrate and fiber content can also influence isoflavone/phytoestrogen metabolism and thereby affect the bioavailability of these bioactive compounds. 133,134 Genistein has been shown to improve endothelial function and upregulate antioxidant genes through ERK1/2 and NFB signaling pathways, both properties that may be beneficial for cardiovascular health.…”
Section: Phytoestrogensmentioning
confidence: 99%
“…After 5 min, the amine shown in Figure 1D was added and stirred for 3 h. The solution was then concentrated and purified by column chromatography using a 60-120 SiO 2 mesh with EtOAc:Hexane (2:8) as eluent to yield compound 12 (0.029 g, 33%). (13). To genistein 2 (0.3 g, 1.1 mmol) in acetone (50 mL) was added K 2 CO 3 (0.53 g, 3.8 mmol) and 1,3-dibromopropane (8.5 mL, 85.3 mmol) and kept stirring at reflux for 24 h. K 2 CO 3 was filtered and the organic layer was concentrated and purified by column chromatography using a 60-120 SiO 2 mesh with EtOAc:Hexane (2:8) as eluent to yield product 13 (0.25 g, 58%).…”
Section: -Hydroxy-3-(4-hydroxy-phenyl)-7-[3-(4-p-tolyl-[123] Triazmentioning
confidence: 99%
“…Studies in the animal models also reported that ERβ might possibly facilitate terminal differentiation in normal mammary glands. 13,24 Estrogen-induced PSN mRNA expression is specifically regulated through ERβ and PSN is a potential downstream marker of ERβ activity. 25 The ratio of ERβ/ERα increased after the treatment with all the three derivatives, as shown in Figure 4B, D and F. The derivative compounds induced the ERβ/ERα ratio to the almost same levels as genistein, but achieved this effect at approximately 10-fold lower doses than genistein.…”
mentioning
confidence: 99%